Aerodynamic design schemes of the inlet guide vane in a core-driven fan stage. (January 2018) - Cao, Hui; Zhou, Zhenggui; Zhang, Jinhuan
A core-driven fan stage operates in both single bypass and double bypass modes. There are large differences in aerodynamic parameters between the two modes. To accommodate the differences, the inlet guide vanes must turn in a very large angle, which may cause significant flow losses. To reduce the flow losses, this article investigates three design schemes in detail using the flow field simulation method. The three schemes investigated include the inlet guide vanes adjusting entirely (Scheme 1), the rear part of the inlet guide vanes adjusting (Scheme 2), and both the front and rear part of the inlet guide vanes adjusting (Scheme 3). Comparisons of the three design schemes suggest that the flow losses in Scheme 1 are higher than those in the other two schemes and that the flow losses in Scheme 3 are not evidently lower than those in Scheme 2. The key geometrical parameters of Schemes 1 and 2 are determined for low flow losses and are used to design the inlet guide vanes. The inlet guide vanes are applied to a core-driven fan stage, and the flow fields are simulated by a three-dimensional flow simulation method to confirm the designs.